Anti-inflammatory properties of methanolic extract of "sikari laharo" (Periploca calophylla) - Adhikari, J.; Thapaliya, S.; Singh, S.; Sah, M. K.; Paudyal, N. (Journal of Agriculture and Forestry University, 2020)
Inflammation, orchestrated in a series of cardinal signs is a pathophysiological condition that occurs during various clinical presentations. Periploca calophylla is a herbal plant which is used traditionally as an anti-inflammatory agent for a myriad of malaises in Nepalese countryside. The scientific research on the anti-inflammatory property of this plant is scanty, and if available elsewhere, its properties are not proven scientifically, except sporadic empirical evidence reported by the traditional faith healers. The main objective of this research was to establish a proof of concept on the anti-inflammatory property of P. calophylla based on the results obtained from a scientific experiment. Accordingly, Adult albino mice animal model was used for in vivo assessment of its property. Three different doses of 80% methanolic extract of the vine of P. calophylla (1.5 mg/ kg, 2 mg/kg, and 2.5 mg/kg) were administered intra-peritoneally to the animals of the test groups. Indomethacin (25 mg/ kg) and distilled water (3 mL/kg) were used as positive and negative controls, via the same route of administration. The anti-inflammatory property was evaluated by the Carrageenan-induced hind paw oedema model test, fresh egg albumin induced paw oedema test, formalin-induced paw oedema test, and haematology. Extract of P. calophylla (1.5 mg/kg) significantly (p<0.01) inhibited inflammatory responses in all the evaluated tests in the animal model. The data obtained from this study indicated that the phyto-extract of P. calophylla possessed a significant amount of anti-inflammatory property. This justifies the empirical and traditional use of this plant as an anti-inflammatory agent. Isolation of the particular compound related to this property needs further experimentation and scientific investigation.